The Role of Social Support and Hardiness on Academic Stress Among Final-Year College Students During COVID-19 Pandemic - Devani, Fadhila; Wulan Saptandari, Edilburga (KnE Social Sciences, 2024)
Writing a thesis during the pandemic added to the burden on student’s minds to the point of causing academic stress. This study is a quantitative survey that aims to determine the role of social support and hardiness on academic stress levels in final-year college students during the COVID-19 pandemic. Data collection was carried out by distributing questionnaires using the Google Form platform which involved 203 subjects. Data processing was carried out using multiple regression techniques. The results showed that social support and hardiness together contributed to academic stress in final-year college students by 10.8% (F = 12.107, p < 0.05). Therefore, the hypothesis proposed in this study is accepted. The implication of this research is an additional information for final-year students that getting social support from an informational standpoint and having hardiness from a commitment standpoint can relieve academic stress experienced while working on their thesis during the COVID-19 pandemic. Keywords: academic stress, COVID-19, final-year college students, hardiness, social support